Relational structure in the global automotive industry: groups, networks and fields - Sacomano Neto, Mário; Matui, Paulo César; Candido, Silvio Eduardo Alvarez; Amaral, Roniberto Morato do (Universidade Federal de São Carlos, 2016)
Purpose: The purpose of this study was to analyze the network structure of automotive companies linked by cross-shareholding, joint ventures, manufacturing contracts and alliances, from 2004 to 2012. The study also explored how the network structure affects the competition in the field. Design/methodology/approach: The sample involved 3695 dyads. Based on this data, it was possible to build and assess networks using Gephi and UCINET software. The study considered network analysis metrics such as centrality, group and network densities temporally. Thus, associated with a contextual and longitudinal analysis, the construction of sociograms allowed visualization of the interactional structure and the automakers’ position in the field. Findings: Results showed that the internationalization and growth of automakers and suppliers are made possible through these relationships among companies (cross-shareholding, joint ventures, manufacturing contracts and alliances). Connections may generate greater power, access to resources and market opportunities. It also enhanced the elaboration of inferences about how these resources influence the competition in the field. Originality/value: The increasing importance of this relational resource shapes the industry competitive structure, which is composed of cooperative and competitive relationships found in meso-level orders.
Estrutura relacional da indústria automobilística mundial: grupos, redes e campos
Keywords: Theory of fields; Fields; Social networks; Strategic groups; Automotive industry; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS